Teachers’ understanding towards concepts and processes of children's literacy - Elfiadi Elfiadi (Aṭfāluna: Journal of Islamic Early Childhood Education, 2021)
This study aims to describe the understanding and process of implementing literacy in early childhood. The method used in this study is a qualitative descriptive method. Data collection techniques were used through observation, interviews, and documentation. The subjects were Early Childhood Education (ECE) teachers in Lhokseumawe. Ten teachers were selected using purposive sampling technique from five kindergartens; Pertiwi Kindergarten, Bunayya, Safiatuddin and Ukhtani. The results showed that: (1) the understanding of ECE teachers in Lhokseumawe interpreted the concept of literacy as a basic skill that children must have in reading, writing, and speaking. Introduction of literacy for early childhood as initial preparation to master reading, writing and speaking skills so that early childhood becomes more prepared to face education at the next level, Elementary School or Madrasah Ibtidaiyah, (2) The process of implementing literacy in ECE institutions is generally carried out in various forms of play activities and children's daily habit and using various forms of methods and media or educational toys.